The relationship between flow experience and teaching well-being of university music teachers: The sequential mediating effect of work passion and work engagement - Wang, Xiaoxiao (Frontiers in Psychology, 2022)
Objective: The purpose of this study was to investigate the relationship between work passion and work engagement among university music teachers in flow experience and teaching well-being. Methods: Using the Flow State Scale, Teacher Well-Being Scale, Work Passion Scale and Work Engagement Scale, 343 university music teachers were tested. Results: Music teachers’ flow experience in kindergarten colleges can predict teaching well-being. University music teachers’ flow experience has an indirect impact on teaching well-being through work passion, and university music teachers’ flow experience has an indirect impact on teaching well-being through work engagement. In addition, work passion and work engagement play a chain-mediating role between university music teachers’ flow experience and teaching well-being. Conclusion: Work passion and work engagement play a chain-mediating role between college music teachers’ flow experience and teaching well-being.